2002
DOI: 10.2486/indhealth.40.42
|View full text |Cite
|
Sign up to set email alerts
|

Skin Problems among Fiber-Glass Reinforced Plastics Factory Workers in Japan.

Abstract: Two surveys, one in winter the other in summer time, examined the skin problems of the entire manual workers (N=148) from 11 small-to-medium sized fiber-glass reinforced plastics (FRP) factories located in Kyushu, Japan. The workers were exposed to unsaturated polyester resin, including styrene and auxiliary agents such as cobalt naphthenate, hardeners such as methyl ethyl ketone peroxides, glass fiber and dust including shortened glass fiber and plastic particles. Eightyseven workers (58.8%) reported having s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Skin symptoms, such as itching, and dermatitis are rather consistently reported in relation to occupational exposure to glass microfibers or other MMVFs in case reports, studies of individual factories, and registry-based studies [10-12,32]. Glass fibers and sensitizers, such as phenol-formaldehyde resin, have been identified as causes for individual cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin symptoms, such as itching, and dermatitis are rather consistently reported in relation to occupational exposure to glass microfibers or other MMVFs in case reports, studies of individual factories, and registry-based studies [10-12,32]. Glass fibers and sensitizers, such as phenol-formaldehyde resin, have been identified as causes for individual cases.…”
Section: Discussionmentioning
confidence: 99%
“…There are even fewer studies on potential non-carcinogenic respiratory effects of glass fibers [6,8,9] and these have provided inconsistent results. There is more consistent evidence of occurrence of skin diseases in glass fiber workers [10,11]. However, we were able to identify only one previous epidemiological study assessing the risk of skin symptoms related to occupational exposures in such industry [12].…”
Section: Introductionmentioning
confidence: 96%
“…Fiberglass‐reinforced plastic (FRP) factory workers are exposed to many chemicals and dust particles in the plastic manufacturing process, including glass fiber exposure . FRP mainly contains fiberglass and epoxy resin . Epoxy resins are widely used for their impact resistance to heat, water, and chemicals, as well as their ability to function as electric insulators and adhesives.…”
Section: High‐risk Populations For Fiberglass Dermatitismentioning
confidence: 99%
“…Fiberglass‐reinforced plastic workers are at high risk of developing occupational dermatitis as a result of the mechanical irritation of the glass fibers and the allergenic properties of epoxy resins. FRPs are used in marine and domestic products including swimming pools and boats . An investigation of FRP workers in Japan showed that 87 of 148 factory workers (58.8%) reported skin irritation, mainly caused by dermatitis …”
Section: High‐risk Populations For Fiberglass Dermatitismentioning
confidence: 99%
See 1 more Smart Citation